Controlled natural language : 5th International Workshop, CNL 2016, Aberdeen, UK, July 25-27, 2016, Proceedings /: 5th International Workshop, CNL 2016, Aberdeen, UK, July 25-27, 2016, Proceedings. (2016) - Unknown
No abstract available